ภาวะผู้นำท้องถิ่นไทยในภาคตะวันออกเฉียงเหนือ: Thai Local Leadership in the Northeast - อนุสุเรนทร์ ชนะวิทย์; เอมอิ่มธรรม สุกัญญา; นิตยสุทธิ์ พิธันดร (Journal of Humanities and Social Sciences (HUSOKKU), 2021)
Abstract The research “Thai Local Leadership in the Northeast” was conducted from January 2009 to March 2010. It focused on the conditions of Thai Local Administration work and its leadership and development approach in relation to meeting citizens’ needs. The study used a sample size of 400 to collect quantitative data and 61 to collect open–ended questionnaire data, as well as 10 in-depth interviews. It was found that the issue requiring the most attention was employment, as citizens reported only medium levels of satisfaction with the help that local leadership had provided in terms of jobs. Respondents desired leaders who were from/residing in the local area, demonstrated morality and ethics, and were paternal in nature, and they viewed leaders’ major role to be coordinating between the state, private, and public sectors. They were partial to leaders who derived their power from their expertise in local administration and work practices and prioritized leadership skills resulting in timely and effective problem-solving. This study recommends leadership development that prioritizes, in descending order: employment, social welfare, public health, environment, education, religion, and culture. Keyword: Thai local leadership